Leadership and Strategy Business in VUCA World - Kuncoro, Setyo; Thaha, Abdurrahman Rahim (Economic Education and Entrepreneurship Journal, 2023)
This research aims to investigate the pivotal role of leadership and business strategy in addressing the challenges of the rapidly changing and uncertain business environment known as VUCA (Volatile, Uncertain, Complex, Ambiguous). In the context of ongoing globalization and technological transformation, organizations are facing increasing pressure to adapt and innovate. This study employs a comprehensive literature review methodology to identify key elements of effective leadership in managing the uncertainty, complexity, diversity, and ambiguity associated with VUCA. The research results yield a leadership and strategy model that integrates essential elements, including adaptive leadership, collaborative leadership, and responsive strategies. This model provides practical guidance for business leaders in developing strategies to tackle VUCA challenges and capitalize on existing opportunities. In a fast-paced business world, a deeper understanding of how to effectively combine these elements becomes the key to long-term success. This research holds significant relevance in understanding how organizations can achieve sustainability in the VUCA era and enhance their competitiveness. The proposed model offers a framework that can be applied across various industry sectors and can assist organizations in facing the challenges of an increasingly uncertain business environment more successfully.Keywords: Adaptation; Business; Leadership; Strategy; VUCA World.DOI: http://dx.doi.org/10.23960/E3J/v6i2.124-132